A model to estimate survival in ambulatory patients with hepatocellular carcinoma: Can it predict the natural course of hepatocellular carcinoma?. Issue 11 (November 2017) - Choi, Won-Mook; Yu, Su Jong; Ahn, Hongkeun; Cho, Hyeki; Cho, Young Youn; Lee, Minjong; Yoo, Jeong-ju; Cho, Yuri; Lee, Dong Hyeon; Cho, Eun Ju; Lee, Jeong-Hoon; Kim, Yoon Jun; et al.
Abstract: Background: Several hepatocellular carcinoma (HCC) staging systems are available including the newly developed staging system, the Model to Estimate Survival in Ambulatory HCC patients (MESIAH); however, whether these staging systems could predict the natural course of HCC is largely unknown. Methods: 1013 patients with history of HCC treatment and 111 patients without any history of treatment till death or last follow-up at a single tertiary hospital were included. Results: The MESIAH score showed a better discrimination ability, with a C-statistic of 0.835 [95% confidence interval (CI), 0.810–0.861] in the group of treated patients compared to the Barcelona Clinic Liver Cancer (BCLC) staging system [0.739 (95% CI, 0.709–0.769)] before propensity score matching. However, the MESIAH score failed to stratify patients according to their risk of death in the group of untreated patients unlike the BCLC staging system. Propensity score matching analysis confirmed that the MESIAH score was most strongly influenced by whether treatment was given or not. Conclusions: Although the MESIAH score provided better prognostic stratification than other staging systems in treated HCC patients, it was not helpful in predicting the natural course of HCC. Since the treatment affects patient outcome and prognosis, it is necessary to develop a new staging system that can also reflect the natural course of HCC.